2003
DOI: 10.1039/b304607a
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactams as versatile synthons for homochiral ibotenate analogues with potential for activity at glutamate receptors1

Abstract: The activated beta-lactam aldehydes 37, 41 and 57 were synthesised. Aldehydes 37 and 57 proved to be more versatile substrates for our "ring switching" strategy to homochiral glutamate antagonists than the corresponding compounds in the pyroglutamate or 6-oxopipecolinate series had been. Substantial libraries of homochiral heteroaromatic glycine derivatives with potential for activity at specific glutamate receptor sub-types were prepared from these aldehydes. The aldehyde 41, containing an additional anion st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…When the aldehyde 119 , prepared from alkene-β-lactam 118 by ozonolysis using dimethyl sulfide as reducing agent, was reacted directly with hydrazine hydrate in methanol at room temperature the epimeric hydroxypyrrolidinones 120 were produced in 62% yield, which are structurally similar to the natural product dealanylalahopcin (Scheme ) 43 …”
Section: 3 Five-membered Heterocycles231 Monocyclic Five-membered Ringsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the aldehyde 119 , prepared from alkene-β-lactam 118 by ozonolysis using dimethyl sulfide as reducing agent, was reacted directly with hydrazine hydrate in methanol at room temperature the epimeric hydroxypyrrolidinones 120 were produced in 62% yield, which are structurally similar to the natural product dealanylalahopcin (Scheme ) 43 …”
Section: 3 Five-membered Heterocycles231 Monocyclic Five-membered Ringsmentioning
confidence: 99%
“…The aldehyde 122 was used directly in the next step without further purification due to its instability. When aldehyde 122 was treated with hydrazine in methanol at room temperature, as in Scheme , the imidazolylglycine 123 was obtained as a white solid in 75% yield . The imidazole formation can be explained by initial hydrazone generation followed by rearrangement to the five-membered ring.…”
Section: 3 Five-membered Heterocycles231 Monocyclic Five-membered Ringsmentioning
confidence: 99%
“…An alternative way of obtaining analogues of ibotenic acid might be to react the pyroglutamate-3-aldehyde 19 with bisnucleophiles and indeed reaction with a substituted hydrazine, as in Scheme 3, might yield isomers 20 of the ibotenate analogues 15, obtained by the b-lactam route. 10 Further, reaction of an enone 21 with substituted hydrazines, as in Scheme 4, might yield the compounds 22, reduced isomers of the ibotenate analogue 14, which was obtained by the b-lactam route. 10 Unfortunately, synthesis of 3-substituted pyroglutamate derivatives such as the aldehydes 19 would best be approached via enones such as 21, and we have shown 11 that such compounds are extremely prone to racemisation and dimerisation under very mild conditions.…”
Section: Methodsmentioning
confidence: 99%
“…10 Further, reaction of an enone 21 with substituted hydrazines, as in Scheme 4, might yield the compounds 22, reduced isomers of the ibotenate analogue 14, which was obtained by the b-lactam route. 10 Unfortunately, synthesis of 3-substituted pyroglutamate derivatives such as the aldehydes 19 would best be approached via enones such as 21, and we have shown 11 that such compounds are extremely prone to racemisation and dimerisation under very mild conditions. We therefore decided to test the route using the reduced compounds 23 and 25.…”
Section: Methodsmentioning
confidence: 99%
“…Examples include the secondary metabolites (S)-willardiine and (S)-isowillardiine, which show interesting pharmacological properties and can act as potent antagonists of AMPA receptors (AMPA = α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) or GluR5-containing kainate receptors (Figure 1, a). [9][10][11][12] Furthermore, it has been demonstrated that peptides containing NBAs show a good intrinsic cell permeability, and form stable complexes with endogenous nucleobases and polynucleotides. [13] In addition, with complementary base pairing at appropriate positions, they can adopt a β-hairpin fold with a unique stability.…”
Section: Introductionmentioning
confidence: 99%